Ocular Signs and Symptoms in Covid-19 patients - Elvita L. Chandra; Laya M. Rares; Rillya D. P. Manoppo (e-CliniC, 2022)
Abstract : Coronavirus Disease 2019 (COVID-19) is an inflammatory lung disease where a person can be infected and infecting other people due to the virus. The only cause of this disease was Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Over 223 countries worldwide was infected and can manifest in pulmonary and extrapulmonary system, one of which is the eye. This study aims to find out some of the ocular symptoms that were found in COVID-19 patients. This study is using the literature review method and the process of data searching using three databases, ClinicalKey, PubMed, and Google Scholar. The keywords used were Ocular Symptoms OR Ocular Manifestations AND COVID-19. The results showed some ocular symptoms that can be found in COVID-19 are ocular pain, itchiness, foreign body sensation, burning sensation, tearing, dry eyes, conjunctival hyperemia, blurred vision, conjunctival discharge, photophobia, and gritty feeling. This findings was obtained in severe cases of patients and some can occur as initial symptoms of COVID-19. In conclusion, ocular symptoms can occur in COVID-19 patients where these symptoms tend to be mild and not always detected on RT-PCR examination using conjunctiva samples. For that reason, using a proper eye protection equipment and avoiding hand-eye contact can prevent the possibility of virus transmission through the eyes.Keywords : COVID-19, Ocular Symptoms, Ocular ManifestationsÂ Â Abstrak : Coronavirus Disease 2019 (COVID-19) adalah sebuah penyakit peradangan paru dimana seseorang dapat terjangkit dan menjangkiti orang lain akibat virus. Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) adalah satu-satunya kausa COVID-19. Penyakit ini telah menginfeksi 223 negara di seluruh dunia dan dapat bermanifestasi pada sistem pulmoner maupun ekstrapulmoner, salah satunya adalah mata. Maksud dari penelitian ini adalah untuk mengetahui beberapa gejala okular yang ikut ditemukan pada pasien COVID-19. Penelitian ini berupa literature review yang dalam proses mencari data memakai 3 database yakni ClinicalKey, PubMed, dan Google Scholar. Kata kunci yang dipakai yakni COVID-19 Ocular Symptoms OR Ocular Manifestations. Hasil penelitian memperlihatkan beberapa gejala okular pada COVID-19 yaitu nyeri pada mata, gatal pada mata, sensasi benda asing, rasa terbakar, mata berair, mata kering, hiperemis konjungtiva, pandangan kabur, adanya sekret di daerah konjungtiva, fotofobia, dan rasa berpasir pada mata. Penemuan ini dapat dijumpai pada kasus berat dan beberapa juga dapat terjadi sebagai tanda awal COVID-19. Simpulan penelitian ini ialah gejala okular dapat terjadi pada pasien COVID-19 dimana gejala ini cenderung ringan dan tidak selalu terdeteksi pada pemeriksaan RT-PCR menggunakan sampel konjungtiva. Untuk itu, penggunaan alat pelindung mata dan menghindari hand-eye contact dapat mencegah kemungkinan transmisi virus melalui mata.Kata kunci : COVID-19, gejala okular, manifestasi okular